PELATIHAN PENGOLAHAN HASIL PERTANIAN DAN PERIKANAN UNTUK PEMBERDAYAAN MASYARAKAT DI DESA BUNUTIN, KECAMATAN BANGLI, KABUPATEN BANGLI - I Ketut Arnawa; I Made Budiasa; Ni G.A.G Eka Martiningsih; Fransiska Penateng Ola; Elisabeth Pandang; Jimmi Ginting (Jurnal Abdi Insani, 2025)
The community service program was carried out in Bunutin Village, Bangli Subdistrict, Bangli Regency, over a period of ten months, involving lecturers, students, and partners, namely local fish farmers and crop farmers. The village has great potential in catfish and tilapia aquaculture as well as in rice and peanut farming. However, it still faces several challenges, including low productivity, limited market access, and a lack of processing knowledge, resulting in production outputs that have not yet achieved optimal added value. The purpose of this activity was to focus on training in the processing of agricultural and aquaculture products as an effort to improve community welfare through the diversification of local products, specifically the production of pepes ikan nila (steamed tilapia in banana leaves). The methods used in this activity included counseling, socialization, demonstration, and direct mentoring, with evaluation conducted through pre-tests, post-tests, observations, and group discussions. Participants were equipped with skills in selecting fresh ingredients, preparing seasonings from local agricultural products, and applying modern processing and packaging techniques, including the use of vacuum and frozen packaging. The evaluation of the counseling and mentoring program on agribusiness analysis was conducted by assessing participants’ understanding through pre-test and post-test questionnaires. The pre-test questionnaire was distributed before the training activity began, while the post-test was administered after the activity was completed. The evaluation results of the training on branding and digital marketing showed an increase in the average level of understanding from 46.16% (less understanding) to 53.8% (understanding). Meanwhile, the evaluation of skills in the agribusiness analysis mentoring showed improvement among participants. The pre-test and post-test results indicated that, on average, 85% of members who were previously rated as “fair” improved to 80% rated as “very good.” In conclusion, this program successfully improved participants’ knowledge and skills in processing agricultural and aquaculture products, while also opening opportunities for sustainable business development.